1999
DOI: 10.1055/s-0037-1614536
|View full text |Cite
|
Sign up to set email alerts
|

First Workshop for Detection of Heparin-induced Antibodies: Validation of the Heparin-induced Platelet-activation Test (HIPA) in Comparison with a PF4/Heparin ELISA

Abstract: Summary Background. No data exist regarding the inter-laboratory reproducibility of the heparin-induced-platelet-activation (HIPA) test, the most widely used functional assay in Germany for the detection of heparin-induced thrombocytopenia (HIT) antibodies. Methods. Nine laboratories used an identical protocol to test eight different sera with the HIPA test. Five laboratories also tested the sera with a platelet factor 4 (PF4)/heparin-complex ELISA. Cross-reactivity with danaparoid-sodium was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
97
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(99 citation statements)
references
References 29 publications
0
97
0
2
Order By: Relevance
“…Therefore, they have much higher specificity for detecting clinically relevant antibodies. However, the performance of these functional assays required experienced staff and is restricted to a few reference laboratories 26. Previous studies showed that the IgM and IgA class of antibodies did not activate platelets, only IgG antibodies can activate platelets via their FcγIIα or IgG-receptors 25.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they have much higher specificity for detecting clinically relevant antibodies. However, the performance of these functional assays required experienced staff and is restricted to a few reference laboratories 26. Previous studies showed that the IgM and IgA class of antibodies did not activate platelets, only IgG antibodies can activate platelets via their FcγIIα or IgG-receptors 25.…”
Section: Discussionmentioning
confidence: 99%
“…This method has been modified to include platelet activation end points other than serotonin release, such as the direct visualization of platelet aggregation (which is widely performed in Europe) 37 or the detection of platelet-derived microparticles by flow cytometry. 38 The major limitation of this assay is its technically demanding nature, 39 and therefore its use is limited to a few reference laboratories. PF4/polyvinyl sulfonate PF4/heparin PF4-dependent fluid-phase immunoassay PF4 particle-gel immunoassay Platelet aggregation studies using citrated platelet-rich plasma † † *Thrombocytopenia broadly defined as a proportional platelet count fall (usually Ͼ 50%).…”
Section: Laboratory Features Of Hitmentioning
confidence: 99%
“…Among these, light transmission aggregometry and MEA have been used to determine heparin/PF4-induced platelet aggregation [39,48,49]. We aimed to use the same methodology to determine HRPR and the functional impact of H/PF4 antibodies for a direct comparison of data.…”
Section: Discussionmentioning
confidence: 99%